Basis of Data Protection Officer Appointment: Comparative Study of Indonesia and European Union Regulation - Putra, Tegar Islami; Fibrianti, Nurul; Fakhrullah, Mohammad Raziq (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The utilization of information technology makes it very easy for a person's Personal Data to be collected and transferred from one party to another without the knowledge of the Personal Data Subject. Personal data controller As a form and effort of protection, it is mandatory to appoint a Data Protection Officer and carry out functions and duties in accordance with the law. To be able to fulfill these functions and duties, it is important to determine the Basis of Data Protection Officer Appointment.Purposes of the Research: The research aims to explain and analyze the comparison of Basis of Data Protection Officer Appointment between Indonesia and Europe Union.Methods of the Research: The research method used in this study is the normative juridical research method with qualitative approach that identifying issues through in-depth analysis of relevant legal regulations concerning the concept of Data Protection Officer Appointment and also employs a comparative study.Results Main Findings of the Research: This study found that the Basis of Data Protection Officer Appointment in Indonesia and the European Union have similar and different aspects of professionalism and ability to fulfill duties. Meanwhile, there are differences in terms of personal data protection practices, where the Indonesian regulation separates knowledge of the law, the practice of Personal Data Protection as the basis for the appointment of data protection officers. Whereas the rules in the European Union combine them so that they have a basis for expert knowledge of data protection law.